The use of digital data analytics in the performance of advertising campaigns: the effect of absorptive capacity - Santos, Silvia Spagnol; Carvalho, Carlos (Review of Business Management, 2023)
Purpose – This study focuses on how the interplay between an advertising firm's absorptive capacity (ACAP) and the use of big data/social media analytics contributes to the performance of advertising campaigns. Theoretical framework – This study extends the theory of the resource and knowledge based views, and that of dynamic capabilities, exploring absorptive capacity in a new context – the advertising industry and the performance of campaigns in Brazil. The influence of the use of external knowledge of big data analytics and social media analytics on the performance of cross-media advertising campaigns in the search for competitive advantage is analyzed. Design/methodology/approach – This study uses structural equation modeling in a sample of 335 advertising agencies (335 questionnaires in all regions of Brazil). Findings – We find that social media analysis led to better performance of advertising campaigns, unlike big data analytics, which was not significant Practical & social implications of research – Questions are raised by highlighting the integrative nature of absorptive capacity and how its components (acquisition, assimilation, transformation, and exploitation) relate to the performance of advertising campaigns. Originality/value – The application of a model to advertising firms is presented, which differs from other industries in its operationalization, pointing out critical theoretical and practical implications. Keywords – big data analytics; social media analytics; advertising campaign performance; absorptive capacity.